QUANTIFYING THE IMPACT OF SOCIAL AND POLITICAL INSTABILITY ON SUPPLY CHAIN OPERATIONS: A RISK ASSESSMENT FRAMEWORK - Bing Wang; Lokhman Hakim Osman; Mohd Rizal Palil; Nurul Atasha Binti Jamaludin (Operational Research in Engineering Sciences: Theory and Applications)
This study examines the effects of social and political unrest, risk management, and climate change on global supply networks. The intention is to expose intricate linkages between components by dismantling the conventional research division. Supply networks are being more impacted by world events. Decisions on strategy must therefore consider the effects of every occurrence. A qualitative study comprising sixteen saturated semi-structured interviews was utilized to guarantee the depth and richness of the data. The three phases of thematic analysis were as follows: formulation of topics, coding, and familiarization with the data. A systematic framework for interpreting data and delving more deeply into the experiences and perspectives of participants was provided by the three-stage theme analysis approach, which was ultimately chosen. This feature enhances the validity of the findings by enabling a meticulous examination of the data while retaining the flexibility to detect emerging trends. The findings of the study offer valuable insights into the complex interconnections among climate change, social and political instability, and risk management in global supply chains. It has been determined that risk mitigation strategies, environmental changes, and geopolitical events are all significant variables that influence supply chain resilience. To mitigate the effects of external uncertainties on disruptions in the supply chain, proactive risk management has grown in significance. This underscores the critical necessity for adaptive approaches to effectively navigate evolving geopolitical and environmental circumstances. This research stands out strategically because of its comprehensive approach, which stresses strong and adaptable supply networks.